Development of Two Scalable Industrial Process for Cinchona Alkaloid Catalyst Recovery: Application to the Large-Scale Production of (+)-Biotin - Xiong, Fei; Li, Xiao-Kang; Xu, Mei; Zhang, Shu-Ping; Chen, Fen-Er; Liao, Bin; Hua, Hao-Jie; He, Jun-Hao (Asian Journal of Chemistry, 2014)
Two scalable chemical processes for the cinchona alkaloid catalyst recovery were demonstrated. In the first approach, the organocatalyst quinine was removed first as the neutral tartrate from alcohol, one recrystallization giving pure salt. Quinine was then recovered in 95 % yield by basification of its aqueous tartrate salt and could be reused without any further purification. In the second approach, the pure quinine catalyst could be easily obtained in almost quantitative yield and with 99 % chemical purity after a single recrystallization from toluene and its spectral data (1H NMR and the value of specific rotation) were in agreement with those of the literature previously reported. The methods are versatile and applicable for industrial-scale synthesis of biologically relevant substance (+)-biotin.